2011
DOI: 10.1002/pola.24986
|View full text |Cite
|
Sign up to set email alerts
|

Titanium complexes based on aminodiol ligands for the ring‐opening polymerization of ε‐caprolactone, rac‐β‐butyrolactone, and trimethylene carbonate

Abstract: Several titanium complexes based on aminodiol ligands were tested as initiators for the ring-opening polymerization (ROP) of e-caprolactone under solution and bulk conditions. All complexes were found to be efficient under both conditions. For bulk polymerization at 70 C, high activities were observed (113.3-156.2 g poly mmol cat À1 h À1 ) together with controlled molar mass distribution. Kinetic studies revealed controlled polymerization, and the chain propagation was first order with respect to monomer conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 54 publications
2
14
1
Order By: Relevance
“…33 The obtained % of CL unit in the copolymer was always reduced with respect to the monomer feed (Table 4). This results are in sharp contrast to the results of the homopolymerization of CL and LA (ROP of CL is much faster than the ROP of LA) under the same polymerization condition 29, 30. Nevertheless, such a behavior seems to be a common feature for the random copolymerization of ε‐CL and LA as it has been reported in the literature earlier 9–14, 19.…”
Section: Resultscontrasting
confidence: 79%
See 1 more Smart Citation
“…33 The obtained % of CL unit in the copolymer was always reduced with respect to the monomer feed (Table 4). This results are in sharp contrast to the results of the homopolymerization of CL and LA (ROP of CL is much faster than the ROP of LA) under the same polymerization condition 29, 30. Nevertheless, such a behavior seems to be a common feature for the random copolymerization of ε‐CL and LA as it has been reported in the literature earlier 9–14, 19.…”
Section: Resultscontrasting
confidence: 79%
“…As expected, when ε‐CL is polymerized at 25°C, dispersity is low 30. Moreover, molar masses evaluated by SEC increased with the growth of the second block.…”
Section: Resultssupporting
confidence: 78%
“…By conducting the reactions over a range of temperatures, it was observed that the overall polymerization rate (k obs ) increases with an increase in temperature as shown in Figure 10 (and supporting information Figures S15 and S16). The semilogarithmic plots shown herein are linear, indicating a first-order dependence of reaction rate with respect to monomer concentration and pass through the origin indicating the absence of an induction period, 81,82 which is in contrast to some previous polymerization reactions using aluminum alkoxides where induction periods were observed. 75,83 This might also imply that the reaction is proceeding via an activated monomer mechanism but it might also be an artifact of the temperatures at which reactions were studied.…”
Section: End Group Analysis By 1 H Nmr Spectroscopy and Maldi-tof Masmentioning
confidence: 58%
“…Results are summarized in Table 1. As expected, when e-CL is polymerized at 25 C, dispersity is low. 30 Moreover, molar masses evaluated by SEC increased with the growth of the second block. For example, when the synthesis of both block was performed at 70 C, molar mass goes from 35180 g mol À1 (PDI ¼ 1.41) for the first PCL SCHEME 1 Titanium alkoxide complexes supported by aminodiol ligands.…”
Section: Synthesis Of Pcl-b-pllamentioning
confidence: 97%
“…21 Recently, we reported the synthesis of titanium complexes supported by aminodiol ligands and their activity toward the ROP of LAs, 29 lactones, and carbonate. 30 In this article, we report our investigation for the synthesis of di and triblock copolymers of e-CL, L-, and rac-LA via living ROP of sequentially added monomers in solution using titanium complexes as initiators. The synthesis of diblock copolymers of trimethylene carbonate (TMC) and e-CL was also studied.…”
mentioning
confidence: 99%